2016
DOI: 10.3390/rs8100867
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Protection Level in the Hydroperiod of Water Bodies on Doñana’s Aeolian Sands

Abstract: Mediterranean temporary ponds on Doñana's aeolian sands form an extensive system of small dynamic water bodies, dependent on precipitation and groundwater, of considerable importance for biodiversity conservation. Different areas of the aeolian sands have received different levels of environmental protection since 1969, and this has influenced the degree of conservation and the flooding dynamic of these temporary surface waters. We use the Landsat series of satellite images from 1985 to 2014 to study the tempo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 36 publications
2
21
0
Order By: Relevance
“…The benefits of changing conditions are already apparent for the Continental European population of black-tailed godwit Limosa limosa limosa with an increasing fraction of their otherwise declining overall population [ 61 ] wintering in southern Spain instead of in traditional wintering areas in West Africa [ 27 ]. In contrast, the steady decline of hydroperiods in our study area [ 2 , 30 , 31 ] has been related to steep declines in several dabbling ducks preferentially selecting deep waters (e.g., common teal Anas crecca , Eurasian wigeon Anas penelope ; [ 26 ], see also [ 8 ] for similar trends in wetlands of Eastern Spain), but also with the disappearance of the diving ferruginous duck ( Aythya nyroca ), which was fairly common in the Doñana wetland complex some decades ago [ 62 ]. There has also been a decline in the common pochard ( Aythya ferina ), and in the red-crested pochard ( Netta rufina ), which were formerly the two most common diving ducks breeding in Doñana, and are currently uncommon breeders [ 63 ].…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…The benefits of changing conditions are already apparent for the Continental European population of black-tailed godwit Limosa limosa limosa with an increasing fraction of their otherwise declining overall population [ 61 ] wintering in southern Spain instead of in traditional wintering areas in West Africa [ 27 ]. In contrast, the steady decline of hydroperiods in our study area [ 2 , 30 , 31 ] has been related to steep declines in several dabbling ducks preferentially selecting deep waters (e.g., common teal Anas crecca , Eurasian wigeon Anas penelope ; [ 26 ], see also [ 8 ] for similar trends in wetlands of Eastern Spain), but also with the disappearance of the diving ferruginous duck ( Aythya nyroca ), which was fairly common in the Doñana wetland complex some decades ago [ 62 ]. There has also been a decline in the common pochard ( Aythya ferina ), and in the red-crested pochard ( Netta rufina ), which were formerly the two most common diving ducks breeding in Doñana, and are currently uncommon breeders [ 63 ].…”
Section: Discussionmentioning
confidence: 93%
“…Water salinity can also create habitat gradients in wetlands by controlling the abundance and composition of primary producers, and hence food availability for herbivorous species like vegetation gleaners and dabbling ducks [ 33 , 48 , 54 – 56 ]. Moreover, rainfall and climatic factors largely dominate the hydrological regime in this area, particularly within the Doñana wetland complex [ 38 ], with most waterbodies flooding annually due to winter rains and drying up in the summer [ 30 , 31 , 57 ]. As the drying period progresses, waterbodies will become saltier, but also shallower, and hence less suitable for diving birds [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have shown that MODIS Global MOD13Q1 NDVI data provides a good source of information for estimating biomass production in a challenging situation-a seasonal marsh characterized by high spatio-temporal variation in precipitation and hydroperiod [55]. While the use of a single image per growth season provided estimates of reasonable quality (39-41% of variance explained in the calibration dataset), modeling the phenological cycle using Land Surface Phenology (LSP) techniques considerably improved the quality and robustness of such estimates (65% and 70% of variance explained using LSP-Maximum-NDVI, in the calibration and the validation datasets, respectively; see also [56]).…”
Section: Discussionmentioning
confidence: 99%
“…These seasonal marshes constitute the largest flooded surface in the Doñana wetlands and are breeding and wintering habitat for many species of European water birds [2]. On the aeolian sand deposits that close the mouth of the Guadalquivir River, there is an extensive system of temporary ponds [34]. Ponds range from small ephemeral pools that flood for a few days or weeks in rainy years to a few large permanent fresh-water lakes.…”
Section: Study Areamentioning
confidence: 99%